The Relationship Between Self-Management and Medication Adherence In Pulmonary Tuberculosis Patients At The Sukarahayu Health Center, Subang Regency - Pipit Ardiansah; Rosiah Rosiah; Minanton Minanton (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Self-management refers to an individual's ability to control aspects of himself, including physical, emotional, mental, and behavioral. Adherence to medication in Pulmonary Tuberculosis Patients is essential because, if not done regularly, it can cause drug resistance, recurrence of the disease, and even death. This study aims to determine the relationship between self-management and medication adherence in Pulmonary Tuberculosis patients at the Sukarahayu Health Center. This research is a type of quantitative research; the research design uses cross-sectional. The sample in this study consisted of 67 respondents, and the sampling technique used was accidental sampling. Data collection used a questionnaire on self-care activities and medication adherence, and data analysis was conducted using the Spearman rank test.The results of the study showed that most respondents had good self-management which was 80.6%, and some respondents had very compliant medication adherence, which was 85.1%. Statistical tests showed a relationship between the self-management variable and medication adherence (p-value 0.001). Conclusion: There is a relationship between self-management and medication adherence in Pulmonary Tuberculosis patients at the Sukarahayu Health Center, Subang Regency. It is hoped that researchers can further explore appropriate efforts or actions for adherence to taking pulmonary tuberculosis drugs.